2016
DOI: 10.2507/26th.daaam.proceedings.104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Lattice Structure Produced by Selective Laser Melting and its Mechanical Properties

Abstract: The quest for light and stiff structures by industries such as the medical industry, the aerospace industry and other industries drives the progress in the additive manufacturing technology. This article is focused on the light-weight Schoen Gyroid cellular structure, which might offer a combination of the desired mechanical properties. The goal is to preserve the lightness of a particular structure while maintaining the desired properties like the rigidity and solidity. Additive manufacturing has a high poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Ataee et al, 35 Maskery et al, 36 Yánez et al, 37 Hanzl et al, 38 Challis et al 39 and Yan et al 40 Hexagonal Honeycomb Anisotropic structure Ju and Summers, 41 Ajdari et al, 42 Zhang et al, 43 Mousanezhad et al 44 and Choy et al 45 (continued)…”
Section: Fcc With Bccz (Fbccz)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ataee et al, 35 Maskery et al, 36 Yánez et al, 37 Hanzl et al, 38 Challis et al 39 and Yan et al 40 Hexagonal Honeycomb Anisotropic structure Ju and Summers, 41 Ajdari et al, 42 Zhang et al, 43 Mousanezhad et al 44 and Choy et al 45 (continued)…”
Section: Fcc With Bccz (Fbccz)mentioning
confidence: 99%
“…123 The excessive powder is then used for the next production to reduce metal powder wastage. 38 The purpose of the heat treatment is to increase the ductility and reduce the pores of the surface of strut. Previous research showed that heat treatment process could enhance the endurance limit.…”
Section: Manufacturing Glsmentioning
confidence: 99%
“…Zaharin et al [6] examined the effect of cell type and pore size on the porosity and mechanical behavior of components made of titanium alloy (Ti-6Al-4V) by additive technology. Hanzl [7] dealt with the influence of the volume ratio of a certain type of porous structures, made by DMLS steel technology on its load-bearing capacity. His publication revealed a relationship between the volume fraction of the entire structure and the load-bearing capacity of the gyroid structure.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The ribs were designed due to the confirmation (or negation) a theory according to which it is not possible to build a wall up to angle 40° without supports. [17] FIGURE I. VIRTUAL MODEL OF THE PART [16] The designed part also includes many holes in various axis directions with diameters from 1 to 10 mm, conical holes and various types of grooves (triangle, trapezoidal and with radius).…”
Section: Component Design and Methods Of Investigationmentioning
confidence: 99%